Transport physics and biorheology in the setting of haemostasis and thrombosis - Brass, Lawrence F. (J Thromb Haemost, 2016)
The biophysics of blood flow can dictate the function of molecules and cells in the vasculature with consequent effects on haemostasis, thrombosis, embolism, and fibrinolysis. Flow and transport dynamics are very distinct for: (1) haemostasis vs. thrombosis and (2) venous vs. arterial episodes. Intraclot transport changes dramatically the moment haemostasis is achieved or the moment a thrombus becomes fully occlusive. With platelet concentrations that are 50–200-fold greater than platelet rich plasma, clots formed under flow have very different composition and structure compared to blood clotted statically in a tube. The platelet-rich, core/shell architecture is a prominent feature of self-limiting hemostatic clots formed under flow. Importantly, a critical threshold concentration of surface tissue factor is required for fibrin generation under flow. Once initiated by wall-derived tissue factor, thrombin generation and its spatial propagation within a clot can be modulated by: γ′-fibrinogen incorporated into fibrin, engageability of FIXa/VIIIa tenase within the clot, platelet-derived polyphosphate, transclot permeation, and reduction of porosity via platelet retraction. Fibrin imparts tremendous strength to a thrombus to resist embolism up to wall shear stresses of 2400 dyne/cm(2). Extreme flows, as found in severe vessel stenosis or in mechanical assist devices, can cause von Willebrand Factor self-association into massive fibers along with shear induced platelet activation. Pathological VWF fibers are ADAMTS13-resistant, but are a substrate for fibrin generation due to FXIIa capture. Recently, microfluidic technologies have enhanced the ability to interrogate blood in the context of stenotic flows, acquired von Willebrand’s disease, hemophilia, traumatic bleeding, and drug action.